Empowering vocational educators instructional delivery through information and communication technology training in universities - Honesta Chidiebere Anorue; Timothy Onwumere Olinya; John E. Ekuma; Lilian O. Nwandu (Journal of Education and Learning (EduLearn), 2023)
This paper explores ways of empowering vocational educators for effective instructional delivery through information and communication technology (ICT) training in tertiary institutions in Enugu State, Nigeria. A descriptive survey research design was used with a population of 63 respondents, comprising lecturers of computer education and business education from University of Nigeria, Enugu State University of Science and Technology, and Godfrey Okoye University. There was no sampling carried out due to the manageable size of the population. The researchers employed a structured questionnaire as a means of collecting data. The collected data were analysed using the mean ( ) and standard deviation. The findings of the study revealed that ICT training would help promote effective instructional delivery in universities in Enugu State. Also, various ICT skills are required by vocational educators for effective instructional delivery. Lastly, several challenges are constraining the ICT training for effective instructional delivery in universities in Enugu State. Based on the findings, the study recommends, among others, that universities should make provision for training and retraining of vocational educators on the use of new technological tools for proper integration in teaching and learning.